Preventing iron deficiency anemia in rural Indonesia: Experiences and support needs of pregnant women and healthcare providers — a qualitative descriptive study - Erli Zainal; Sri Sulistyowati; Agung Wibowo; Widiyanto Widiyanto (Belitung Nursing Journal, 2026)
Background: Iron deficiency anemia remains a significant public health concern among pregnant women, particularly in rural areas of low- and middle-income countries. Despite routine antenatal care services and iron–folic acid supplementation programs, adherence to supplementation and effective anemia prevention remain challenging. Understanding how pregnant women and healthcare providers experience and respond to these challenges is essential for strengthening anemia prevention efforts in rural maternal health services. Objective: This study aimed to explore the experiences and support needs of pregnant women and healthcare providers in preventing iron deficiency anemia in rural Indonesia. Methods: A qualitative descriptive study was conducted in Seluma Regency, Bengkulu Province, Indonesia, between May and August 2025 using in-depth interviews and focus group discussions. A total of 30 participants (18 pregnant women and 12 healthcare providers, consisting of six midwives and six nutritionists) were recruited using purposive sampling through antenatal care services. Data were collected using semi-structured interview guides and analyzed using inductive thematic analysis following Braun and Clarke's approach. Results: Three themes emerged from the thematic analysis: (1) understanding anemia beyond symptoms, (2) challenges in maintaining consistent iron–folic acid supplementation, and (3) perceived structural constraints in antenatal counseling. Pregnant women demonstrated limited understanding of anemia beyond physical symptoms, which was compounded by low educational levels prevalent in the sample. Barriers to consistent supplementation included forgetfulness, side effects, and uncertainty about proper tablet intake. Healthcare providers reported that high patient volumes and limited consultation time constrained their ability to deliver comprehensive counseling and follow-up support. Conclusion: The findings demonstrate that the routine provision of iron–folic acid supplements alone are insufficient to support consistent adherence. Strengthening continuous and practical support within antenatal care through nursing- and midwifery-led education and follow-up is essential to improve anemia prevention in rural maternal health services. Strategies should be tailored to address low health literacy, daily behavioral barriers, and structural service constraints to achieve meaningful improvements in maternal anemia prevention.